Effekte der App Phontasia auf die Lese- und Rechtschreibleistungen von Zweitklässlern - Nadine Pflaumer (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Reading and spelling skills of primary school children show a wide spread of ability. Therefore, teachers must provide a range of individual learning methods. Use of methodologically and empirically tested apps could provide support here. Phontasia is an app for iPad that trains graphem-phoneme-correspondence to support orthographic knowledge for lexical reading and writing. On the basis of N=50 children (age M=8,3 years; 28 boys, 22 girls), a pre-post-follow-up-Design was used to investigate the short-term and long-term efficacy of the Phontasia app. The children of the Phontasia group trained with the app 35-40 minutes once a week for six weeks with the app in a school setting. The control group took part in regular German lessons. Both groups worked with the same textbook, but had different teachers. The study focused on the different stages of development of direct and indirect processing strategies. It was also of interest whether the intervention increased naming speed for colours, letters, and numbers and their correlation with reading and spelling performance. The intervention with the Phontasia app shows a significant immediate and sustained effect on spelling performance when compared to the control group. Short term effects occurred in reading and naming speed for numbers and could not be confirmed in the follow-up study. As expected, correlations confirmed a relationship between naming speed and reading speed. Based on these results, the app Phontasia seems to be a useful and economic tool for the promotion of spelling in class settings while accommodating for individual learning styles.